Modulation of Microbiota and its Impact on Depression - Maparu, Kousik (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Gut microbial flora is the largest micro-ecosystem in the human body, it is symbiotically associated with the host; and maintains normal physiological processes in a dynamic equilibrium state. A plethora of evidence supports that gut microbial flora influences the neurotransmitters of the central nervous system. This gut flora influences cognitive function, anxiety, depression; and mood disorders as they are capable of synthesizing neurotransmitters in the nervous system. Therefore intake of probiotics influences gut microbiome; and depression. The versatility and number of gut microbial flora varies individually, so the content of common gut microbes may affect the neurotransmitters, manipulating the gut microbiota with probiotics offers a novel approach to treat brain disorders such as depression via GUT-BRAIN AXIS. The present review outlines the aspect of such alterations and how modulation of gut microbiota influences depression.